2021
DOI: 10.1111/ocr.12514
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of hand‐wrist maturation stages based on cervical vertebrae images using artificial intelligence

Abstract: Objective: To predict the hand-wrist maturation stages based on the cervical vertebrae (CV) images, and to analyse the accuracy of the proposed algorithms. Settings and population:A total of 499 pairs of hand-wrist radiographs and lateral cephalograms of 455 orthodontic patients aged 6-18 years were used for developing the prediction model for hand-wrist skeletal maturation stages. Materials and Methods:The hand-wrist radiographs and the lateral cephalograms were collected from two university hospitals and a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…Los periodos de crecimiento y desarrollo mediante radiografías cárpales y las comparo con el análisis de una radiografía cefálica lateral por 24 modelos diferente de ANN; luego relacionaron el nivel de maduración y se pudo observar correlaciones significativamente positivas entre los datos de la radiografía carpal y los niveles de desarrollo del crecimiento vertebral cervical y la edad (p < 0,001) siendo el de mayor exactitud el modelo (17,19). Kim et al hiso la misma comparación usando 8 modelos de ML, "ayesianRidge", "LinearRegression, HuberRegressor", "SGD Regressor", "RandomForest Regressors", "TheilSen Regressor", "AdaBoost Regressor" y "LinearSVR" de los cuales las Medidas de error absoluto, Medidas de error absoluto redondeadas y raíz cuadrada de las medidas de error absoluto tuvieron 0.90, 0.87 y 1.20, respectivamente, dando un alto grado de correlación entre ambas, y con información adicional como la edad y el sexo se convierte en una herramienta muy útil en la toma de decisiones para la edad de tratamiento optima en pacientes en crecimiento (20).…”
Section: Discussionunclassified
“…Los periodos de crecimiento y desarrollo mediante radiografías cárpales y las comparo con el análisis de una radiografía cefálica lateral por 24 modelos diferente de ANN; luego relacionaron el nivel de maduración y se pudo observar correlaciones significativamente positivas entre los datos de la radiografía carpal y los niveles de desarrollo del crecimiento vertebral cervical y la edad (p < 0,001) siendo el de mayor exactitud el modelo (17,19). Kim et al hiso la misma comparación usando 8 modelos de ML, "ayesianRidge", "LinearRegression, HuberRegressor", "SGD Regressor", "RandomForest Regressors", "TheilSen Regressor", "AdaBoost Regressor" y "LinearSVR" de los cuales las Medidas de error absoluto, Medidas de error absoluto redondeadas y raíz cuadrada de las medidas de error absoluto tuvieron 0.90, 0.87 y 1.20, respectivamente, dando un alto grado de correlación entre ambas, y con información adicional como la edad y el sexo se convierte en una herramienta muy útil en la toma de decisiones para la edad de tratamiento optima en pacientes en crecimiento (20).…”
Section: Discussionunclassified
“…Keypoint-based analysis of medical images is a widely used approach in clinical treatment [1,6,8,18,26]. Anatomical points obtained from an image can be utilized to measure significant features of body parts where keypoints are located.…”
Section: Introductionmentioning
confidence: 99%
“…Anatomical points obtained from an image can be utilized to measure significant features of body parts where keypoints are located. For example, vertex points of cervical vertebrae can be used to measure the concavity and height of the vertebrae, which correlates to skeletal growth [6,18]. Usually, doctors manually annotate such keypoints, but the process is costly, requiring The goal is to estimate (a) 13 keypoints on the cervical vertebrae, each of which determines vertebrae morphology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two groups of Kim et al and Kök et al evaluated the automated diagnosis of skeletal maturation using cervical vertebrae images on cephalometry and that AI‐based decision supporting is available for evaluating the optimal timing of treatment for growing orthodontic patients 18,19 . Both groups also found that that additional patient information increased the accuracy of the prediction.…”
mentioning
confidence: 99%